Preservação e conservação do patrimonio documental no arquivo público do Pará: uma análise dos documentos digitalizados “mão de obra negra escravizada na amazônia e seus descendentes” - FURTADO, Fátima do Rosário Josino (2017)
In this research, an attempt was made to analyze the importance of APEP in the preservation of the collection "Black labor enslaved in the Amazon and its descendants", since these documents preserved / guarded have a relation with the History of a people. In this sense, the general objective of this research is to understand the preservation and preservation of the documentary heritage of the Public Archive of the State of Pará, represented in the collection "Black Workman enslaved in the Amazon and its descendants." As a methodology, this project is characterized by being an exploratory / descriptive and qualitative research, while type is a case study. A questionnaire was applied with 51 questions about the institution in general, and an interview with 10 questions about the "Black Handcuffed Slavery in the Amazon and its Descendents" collection, as well as a technical visit to the archive. It is concluded that the preservation and conservation of the collections in the APEP are precarious due to several problems of infrastructure and lack of investment of the State Government, and therefore, the rich historical collection of the institution runs a serious risk of documentary loss. The "Black Handicraft" collection, which is in the process of being digitalized, is receiving the same treatment for its conservation by means of digitization, and runs the same risks of the other collections because it is under the same inadequate storage conditions as other documents. An urgent policy involving political, administrative and organizational measures and actions regarding the preservation and preservation of the APEP's historical heritage is necessary.